Phụ thuộc không gian của tham nhũng ở Việt Nam - Lê Quang, Cảnh; Đặng Trung, Chính (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
Previous studies on corruption have seldom addressed the spatial effects of corruption. This paper argues that there is a contagion of corruption across provinces in Vietnam. Using a balanced panel dataset adapted from the Provincial Competitiveness Index survey and General Statistical Office, this study tests and concludes that the Spatial Durbin Model with the fixed effects is consistent for the research sample. Empirical results suggest the existing spatial effects of corruption among Vietnamese provinces. The spatial spillover effects of corruption can be explained by learning effects from interprovincial migrants and provincial governance proxied by transparency and the rule of law. The empirical results shed the light on proposing anti-corruption measures and policies to mitigate spatial corruption spillovers across provinces in Vietnam